Research on lightning surge overvoltage of convertor station with 500 kV hot‐standby circuit breakers. Issue 7 (1st October 2015) - Fan, Youping; Wu, Lihui; Qiu, Huimin; Wen, Wu; Liu, Songkai; Qian, Hai; Chen, Dong
Abstract : This study introduces a circuit breaker flashover accident caused by lightning strokes in a row of Xingren convertor station in Guizhou. To find out the reason of the flashover and whether fault circuit breaker insulation coordination can meet requirements under multiple lightning strikes, the overvoltage condition of hot‐standby circuit breakers under lightning surge is calculated and checked by using EMTP and full‐scale high impulse voltage test of the fault circuit breaker is conducted for the first time. Owing to the hot‐standby state of the circuit breaker, the flashover accident is more likely to happen when lightning surge invades the substation or convertor station again. Measures to improve the hot‐standby circuit breakers' lightning withstand level are proposed and by simulating analysis, the measure combined installing a line arrester at a tower of the inlet line and installing an arrester near a certain breaker on the line proves to be effective.